CONTENT AND ESSENCE OF GAME TECHNOLOGY. DIDACTIC GAME TECHNOLOGY AND ITS PRACTICAL SIGNIFICANCE (Conferencea, 2023)
In advance, the teacher should divide each lesson into certain parts and determine what to pass (teaching) in which part and what it consists of. Then, when the students feel bored, tired or psychological changes during the lesson, it is necessary to introduce a short-term didactic game adapted to the topic in order to add new content to the students' educational activities. Then, students' attention will be focused on the news, and their activity will increase. In such a situation, with the help of the proposed game, it will be possible to master the subject in full on time.